(NfIZI^ESKIE SWOJSTWA WE]ESTWA I PROCESSY W NEDRAH zEMLI (B:s ((NmATERIALY (B1-(NJ wSESO@ZNOJ GEOFIZI^ESKOJ [KOLY (B) /s - (NvARKOW(B, (NwLADIMIR nAUMOWI^s; (NwSESO@ZNAQ GEOFIZI^ESKAQ [KOLA (B(1) (NzWENIGOROD (B1984s ((NmOSKWA (B:s (NiN(B-(NTA FIZIKI zEMLI an sssr(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE DOKL(B.s
(Nw NADZAG(B.: (Nan sssr(B, (NiN(B-(NT FIZIKI zEMLI IM(B. (No(B.(N`(B. (N{MIDTAs
Keywords: (NgEOFIZIKAs